Aesthetics and the cinematic narrative : an introduction - Bolus, Michael Peter (Anthem Press, 2019)
Since the inception of cinema in the late nineteenth century, filmmakers have employed a wide array of precursory aesthetic strategies in the conception and creation of their disparate works. The existence of these traditional antecedents have afforded filmmakers a diverse range of technical and artistic applications towards the construction of their cinematic narratives. Furthermore, the socio-political and cultural contexts in which films are conceived often inform the manner in which particular aesthetic sensibilities are selected and deployed. Unfortunately, many creative artists - and audiences - remain unfamiliar with Aesthetics as a practical discipline and how it might apply to their own creative and/or interpretive pursuits. 'Aesthetics and the Cinematic Narrative' provides a concise historical survey of Aesthetics as a philosophical discipline and applies several of its underlying principles to the examination of filmic storytelling. The book's four chapters codify working definitions of the relevant terms and concepts, employing specific case studies to illustrate how certain aesthetic stratagems govern a film's structural design and execution. By drawing connections between the technical/creative decisions filmmakers must make and more time-honoured traditions regarding the nature of art, the structures of storytelling and the import of visual imagery, 'Aesthetics and the Cinematic Narrative' helps recontextualize film within a wider sphere of artistic/intellectual endeavour. The book is a useful and much-needed addition to the pre-existing canon for students of visual storytelling and for general readers